2011
DOI: 10.1375/ajgc.21.2.175
|View full text |Cite
|
Sign up to set email alerts
|

Mediator and Moderator Role of Loneliness in the Relationship Between Peer Victimization and Depressive Symptoms

Abstract: The goal of this study was to examine the mediator and moderator roles of loneliness in the relationship between peer victimisation and depressive symptoms. The participants of the study were 144 adolescents (66 girls, 78 boys) ranging in age from 11 to 15 years. Hierarchical multiple regression analyses were conducted to test the relations of peer victimisation to depressive symptoms through the mediating role of loneliness, as well as examining the joint and independent effects of loneliness and victimisatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 41 publications
2
13
0
2
Order By: Relevance
“…Social-cognitive processes might be less salient than emotional processes and might be less relevant in explaining why peer victimization affects adjustment and wellbeing. The summary of the reviewed studies suggests that explanations might generally be quite complex because chain mediations are likely where, for instance, peer victimization increases loneliness (Baker and Bugay 2011), which results in more depressive symptoms, which, in turn, predict higher anxiety (Hamilton et al 2016). Future studies are needed that elucidate the sequence of consequences of peer victimization.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Social-cognitive processes might be less salient than emotional processes and might be less relevant in explaining why peer victimization affects adjustment and wellbeing. The summary of the reviewed studies suggests that explanations might generally be quite complex because chain mediations are likely where, for instance, peer victimization increases loneliness (Baker and Bugay 2011), which results in more depressive symptoms, which, in turn, predict higher anxiety (Hamilton et al 2016). Future studies are needed that elucidate the sequence of consequences of peer victimization.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas some studies relied exclusively on the Baron and Kenny approach of mediation testing (1986) where mediation is inferred from comparing direct effect sizes with and without controlling for the mediating variable, studies increasingly used Hayes' well-documented and freely available SPSS macro PROCESS (e.g., Casement et al 2014;Guarneri-White et al 2015;Hamlat et al 2015;Mathieson et al 2014). Such novel approaches are needed to estimate possible double-and multiple-mediation, as are larger sample sizes than used in some of the studies reviewed here (e.g., Baker and Bugay 2011;Espinoza 2015;Giannotta et al 2012;Guarneri-White et al 2015;Harper 2012;Jenkins and Demaray 2015, who all used samples smaller than n = 200). Adolescent Res Rev (2016) 1:341-356 351 In addition to small sample size in some of the studies reviewed here, other limitations need to be noted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also commonly experience restricted physical movements, which decreases their social activities and further escalates their psychological distress (Fry & Debats, 2002;Luo et al, 2012). Moreover, the elderly's tendency to socially withdraw often reduces the size of their social network and leads them to social isolation (Baker & Bugay, 2011). From the extant literature, we found that negative feelings, social isolation, and social participation are associated (Steptoe et al, 2013), but research has explored how they influence each other less often.…”
Section: Literature Reviewmentioning
confidence: 94%
“…Price (2011) juga melaporkan bahwa Bupro pion merupakan terapi psikofarmakologis yang efektif untuk menangani persoalan kecanduan gim daring dan depresi yang komorbid atau berasosiasi dengan kecanduan tersebut. Dari ketiga laporan penelitian tersebut, dapat digambarkan relasi-relasi antar variabel sebagai berikut: 1) Relasi dengan Sebaya  Kesepian  Simtom Depresif (Baker & Bugay, 2011). 2) Simtom Depresif  Judi Patologis (O'Brien, 2011) atau Kecanduan Gim Daring (Price, 2011).…”
Section: Hasil Dan Pembahasanunclassified